KNOWLEDGE ABOUT CLEAN AND HEALTHY LIVING BEHAVIOR (PHBS) WITH THE INCIDENT OF DIARRHEA IN SCHOOL-AGED CHILDREN AT SMP 1 INGIN JAYA - Najikhah, Nur; Hidayattullah, Mhd; Sari, Ema Novita (Jurusan Kesehatan Lingkungan, Poltekkes Kemenkes Aceh, 2023)
Health problems, especially those related to clean and healthy living behavior, are prone to school-aged children. Some diseases that are often found in school-aged children include diarrhea, caries and dengue fever. Prevention of this problem can be done through a clean and healthy living behavior program. Indicators of clean and healthy living behavior in educational institutions/schools include washing hands with running water and using soap, consuming healthy snacks in the school canteen, using clean and healthy latrines, regular and measured exercise, eradicating mosquito larvae, not smoking in school, weighing and measuring height, and throwing rubbish in the right place. The aim of this research is to describe clean and healthy living behavior among school children. The research method uses a quantitative method with a descriptive approach, the samples used in this research were 50 samples, then data processing used the Microsoft Excel computer program. The results of the research show that hand washing behavior is in the category of healthy snacks in the Good category. Based on the research results, it can be concluded that the PHBS students of SMP Negeri 1 Ingin Jaya are still in the deficient category.